2020
DOI: 10.1002/jemt.23553
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of microbial mediated cadmium oxide nanoparticles

Abstract: Microbial mediated synthesis of metallic nanoparticles constitutes as effective and promising approach for the development of antibacterial materials in the field of bioengineering and biomedicine. We prepared Cadmium oxide nanoaprticles (CdO NPs) utilizing Penicillium oxalicum, and cadmium acetate solution via coprecipitate method. The elemental composition and morphology of these synthesized CdO NPs were examined through X-ray diffraction (XRD), UV-Vis absorption spectroscopy, Fourier transform infrared spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 84 publications
4
21
0
Order By: Relevance
“…These results were expected since it is reported that polyphenolic extracts are more effective against Gram-positive bacteria. Gram-negative microorganisms have a unique cell structure, with a double phospholipidic layer, which is responsible for the low susceptibility of these bacteria due to the repulsion between PC and the lipopolysaccharide present on the surface of the bacteria membrane [53]. According to the literature, bacteria from the Staphylococcus family, are the most susceptible to the action of PC, which is compatible with the obtained results [52,54].…”
Section: Antimicrobial Capacitysupporting
confidence: 87%
“…These results were expected since it is reported that polyphenolic extracts are more effective against Gram-positive bacteria. Gram-negative microorganisms have a unique cell structure, with a double phospholipidic layer, which is responsible for the low susceptibility of these bacteria due to the repulsion between PC and the lipopolysaccharide present on the surface of the bacteria membrane [53]. According to the literature, bacteria from the Staphylococcus family, are the most susceptible to the action of PC, which is compatible with the obtained results [52,54].…”
Section: Antimicrobial Capacitysupporting
confidence: 87%
“…JDX-3432, JEOL, Japan was used for XRD pattern analysis of the synthesized nanoparticles, following the protocol of Asghar et al [ 39 ]. The average size of crystallite was measured using Debye–Scherrer equation, which is calculated by D = k λ/βcosθ,…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced DPPH radical quenching activity was noted in S. lycopersicum samples treated with compost infused with plant growth promoting bacteria. Mechanism related to enhanced antioxidant activity could be due to the elevation in the expression of antioxidant genes that confer homeostasis in the plant metabolism (64,65). Cucumis sativus infused with Promicro monospora, Burkholdera cepacia, and Acinetobacter calcoaceticus showed enhanced phenol production due to upregulation of antioxidant enzymes (66).…”
Section: Antioxidant Activitymentioning
confidence: 99%